Dampak Implementasi Marketing Mix Terhadap Hasil Dan Tingkat Kepuasan Pasien Yang Sedang Dirawat Di Rumah Sakit Umum - Jilva Triyanti; Anisa Kholifatun (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to explore the impact of marketing mix implementation on the results and level of satisfaction of patients being treated at a public hospital. By collecting data through questionnaires and statistical analysis, this research evaluates the relationship between marketing mix elements (product, price, promotion and distribution) with patient treatment outcomes and their level of satisfaction. The findings from this study provide valuable insights for hospitals in improving service quality and patient satisfaction.